Reconocimiento del niño con síndrome de Down como un sujeto de crianza (2013)
ABSTRACT: o describe how the children with Down`s syndrome are recognized by mothers as subjects of parenting and accompaniment. Methodology: an ethnographic study whose participants were 20 mothers of children with Down’s syndrome. Data were collected using semi-structured interviews and field observations. Similarly, this study included a categorical analysis and a literature review. Results: given the cultural and social conceptions regarding this condition, mothers experience sadness and anxiety upon giving birth to a child with Down’s syndrome. Despite this, and thanks to coexistence and to the mother-child bond, the child is later perceived as a subject of parenting who is equal to another person without the syndrome. Discussion: children become social subjects when they achieve their goals in growth and development, and mothers can perceive this. Conclusion: by living with their sons, the mothers participating in this study discovered that their sons emerge as social persons with Down’s syndrome. The mothers also discovered that these individuals have their own potential and that it is possible to accompany them through parenting and therefore to realize themselves as mothers.